Dose-dependent effects of endosulfan and malathion on adult wistar albino rat ovaries - KAYHAN, FİGEN ESİN; SESAL, NÜZHET CENK (My University, 2009)
In this sludy, histological effects and malondialdehyde (MDA) levels were investigated by endosulfan and malathion in adult female rat ovaries. An increase of MDA level in rat ovarium tissues due to endosulfan and malathion may be an indicator of the tree radicals occurred during the metabolism and their lipid peroxidative inducing damage. In this study in accordance with the biochemical findings, the study demonstrated that there are pronounced structural defects in histological examinations of ovarian tissues in rats which were administered endosulfan and malathion. It has been observed that the size of ovarian tissues of rats which were administered endosulfan and malalhion in different doses was decreased in various levels. There was a significant decrease healthy follicles and a significant increase atretic follicles in low dose of endosulfan and malathion (11 mg kg-1) treated rats The histologic observations of the ovary revealed the presence of less number of healthy follicles and more number of atretic follicles and corpus Intcums in high dose of endosulfan and malathion (33 mg kg-1} treated rats. Finally, a peroxidative damage occurs inavitably due lo endosulfan and malathion for ovarium tissues. The biochemical results (MDA levels) also showed such a damage, similar with the histological results. © 2009 Asian Network for Scientific Information.
Keywords: Histopathological effects; Malondialdehyde; Pesticide